CPI-637 as a Potential Bifunctional Latency-Reversing Agent That Targets Both the BRD4 and TIP60 Proteins - Zheng, Tengyi; Chen, Pei; Huang, Yifan; Qiu, Jiayin; Zhou, Chenliang; Wu, Ziyao; Li, Lin (Frontiers in Cellular and Infection Microbiology, 2021)
The failure of highly active antiretroviral therapy (HAART) has been largely responsible for the existence of latent human immunodeficiency virus type 1 (HIV-1) reservoirs. The “shock and kill” strategy was confirmed to reactivate HIV-1 latent reservoirs by latency reversing agents (LRAs) for accelerated HIV-1 clearance. However, a single LRA might be insufficient to induce HIV-1 reactivation from latency due to the complexity of the multiple signaling regulatory pathways that establish the HIV-1 latent reservoir. Therefore, combinations of LRAs or dual-mechanism LRAs are urgently needed to purge the latent reservoirs. We demonstrate here for the first time that a dual-target inhibitor with a specific suppressive effect on both BRD4 and TIP60, CPI-637, could reactivate latent HIV-1 in vitro by permitting Tat to bind positive transcription elongation factor b (P-TEFb) and assembling Tat-super-elongation complex (SEC) formation. In addition, CPI-637-mediated TIP60 downregulation further stimulated BRD4 dissociation from the HIV-1 long terminal repeat (LTR) promoter, allowing Tat to more effectively bind P-TEFb compared to BRD4 inhibition alone. Much more importantly, CPI-637 exerted a potent synergistic effect but alleviated global T cell activation and blocked viral spread to uninfected bystander CD4+ T cells with minimal cytotoxicity. Our results indicate that CPI-637 opens up the prospect of novel dual-target inhibitors for antagonizing HIV-1 latency and deserves further investigation for development as a promising LRA with a “shock and kill” strategy.